Applying citizen science for malaria prevention in Rwanda: An integrated conceptual framework. (1st November 2018) - Asingizwe, Domina; Poortvliet, P. Marijn; Koenraadt, Constantianus J.M.; Van Vliet, Arnold J.H.; Murindahabi, Marilyn M.; Ingabire, Chantal; Mutesa, Leon; Feindt, Peter H.
Abstract: Malaria remains a major threat to public health. Long-Lasting Insecticide-treated Nets (LLINs) and Indoor Residual Spraying (IRS) have been widely adopted as important malaria prevention and control interventions and have contributed to significant reduction in malaria incidence. However, recently malaria resurgence has been reported in different countries, including Rwanda, indicating that current attempts to control and eliminate malaria may be failing due to environmental changes and changes in human behaviour. Engaging citizens in malaria prevention and control would help them to identify and prioritize their own health concerns and be able to make appropriate decisions. A citizen science approach to monitor ecological changes by providing timely information is likely to support more effective and consistent use of malaria prevention and control interventions. However, the application of citizen science in malaria prevention and control has lagged behind when comparing with areas of disease diagnosis and treatment. In addition, the determinants of participation in such a citizen science program have not been fully analyzed. This paper presents a conceptual model of likely determinants of participation in connective action (sharing and exchange of malaria-related information), effective and consistent use of malaria preventive and control measures (LLINs and IRS) and collective action (participating in public goods for malaria prevention). The model will guide future research on behavioural and contextual factors and may enhance the effective and consistent use of malaria preventive and control interventions.